Dupilumab in children aged 6 months to younger than 6 years with uncontrolled atopic dermatitis: a randomised, double-blind, placebo-controlled, phase 3 trial. Issue 10356 (17th September 2022) - Paller, Amy S; Simpson, Eric L; Siegfried, Elaine C; Cork, Michael J; Wollenberg, Andreas; Arkwright, Peter D; Soong, Weily; Gonzalez, Mercedes E; Schneider, Lynda C; Sidbury, Robert; Lockshin, Benjamin; Meltzer, Steven; et al.
Summary: Background: Current systemic treatments for children younger than 6 years with moderate-to-severe atopic dermatitis that is uncontrolled with topical therapies might have suboptimal efficacy and safety. Dupilumab is approved for older children and adults with atopic dermatitis and for other type 2 inflammatory conditions. We aimed to evaluate efficacy and safety of dupilumab with concomitant low-potency topical corticosteroids in children aged 6 months to younger than 6 years with moderate-to-severe atopic dermatitis. Methods: This randomised, double-blind, placebo-controlled, parallel-group, phase 3 trial was conducted in 31 hospitals, clinics, and academic institutions in Europe and North America. Eligible patients were aged 6 months to younger than 6 years, with moderate-to-severe atopic dermatitis (Investigator's Global Assessment [IGA] score 3–4) diagnosed according to consensus criteria of the American Academy of Dermatology, and an inadequate response to topical corticosteroids. Patients were randomly assigned (1:1) to subcutaneous placebo or dupilumab (bodyweight ≥5 kg to <15 kg: 200 mg; bodyweight ≥15 kg to <30 kg: 300 mg) every 4 weeks plus low-potency topical corticosteroids (hydrocortisone acetate 1% cream) for 16 weeks. Randomisation was stratified by age, baseline bodyweight, and region. Patient allocation was done via a central interactive web response system, and treatment allocation was masked. The primary endpoint at week 16 was the proportion of patients with IGA score 0–1 (clear or almost clear skin). The key secondary endpoint (coprimary endpoint for the EU and EU reference market) at week 16 was the proportion of patients with at least a 75% improvement from baseline in Eczema Area and Severity Index (EASI-75). Primary analyses were done in the full analysis set (ie, all randomly assigned patients, as randomly assigned) and safety analyses were done in all patients who received any study drug. This study was registered with ClinicalTrials.gov, NCT03346434 . Findings: Between June 30, 2020, and Feb 12, 2021, 197 patients were screened for eligibility, 162 of whom were randomly assigned to receive dupilumab (n=83) or placebo (n=79) plus topical corticosteroids. At week 16, significantly more patients in the dupilumab group than in the placebo group had IGA 0–1 (23 [28%] vs three [4%], difference 24% [95% CI 13–34]; p<0·0001) and EASI-75 (44 [53%] vs eight [11%], difference 42% [95% CI 29–55]; p<0·0001). Overall prevalence of adverse events was similar in the dupilumab group (53 [64%] of 83 patients) and placebo group (58 [74%] of 78 patients). Conjunctivitis incidence was higher in the dupilumab group (four [5%]) than the placebo group (none). No dupilumab-related adverse events were serious or led to treatment discontinuation. Interpretation: Dupilumab significantly improved atopic dermatitis signs and symptoms versus placebo in children younger than 6 years. Dupilumab was well tolerated and showed an acceptable safety profile, similar to results in older children and adults. Funding: Sanofi and Regeneron Pharmaceuticals